PEMANFAATAN SITUS GANDOANG DALAM PEMBELAJARAN DENGAN METODE DISCOVERI LEARNING PADA MAHASISWA PROGRAM STUDI PENDIDIKAN SEJARAH - Wulan Sondarika (Jurnal Artefak, 2019)
The discovery method in historical learning with the theme of the Gandoang site as a learning medium aims to train students to analyze past events and the benefits of the Gandoang site as a source of learning history and local tourism. The research method in this study is qualitative. Qualitative research is a research procedure that produces descriptive data in the form of written or oral words from people and observed behavior. The results of the study that after analyzing the learning process with the discoveri method were very helpful for lecturers in creating an active, educative and enjoyable learning atmosphere and could stimulate students to think critically and creatively in finding independent learning resources.